CD4R cell count at antiretroviral therapy initiation and economic restoration in rural Uganda - Venkataramani, Atheendar S.; Thirumurthy, Harsha; Haberer, Jessica E.; II, Yap Boum; Siedner, Mark J.; Kembabazi, Annet; Hunt, Peter W.; Martin, Jeffrey N.; Bangsberg, David R.; Tsai, Alexander C. (Aids, 2014)
Objective: To determine whether earlier initiation of antiretroviral therapy (ART) is associated with better economic outcomes. Design: Prospective cohort study of HIV-positive patients on ART in rural Uganda. Methods: Patients initiating ART at a regional referral clinic in Uganda were enrolled in the Uganda AIDS Rural Treatment Outcomes study starting in 2005. Data on labor force participation and asset ownership were collected on a yearly basis, and CD4þ cell counts were collected at pre-ART baseline. We fitted multivariable regression models to assess whether economic outcomes at baseline and in the 6 years following ART initiation varied by baseline CD4þ cell count. Results: Five hundred and five individuals, followed up to 6 years, formed the estimation sample. Participants initiating ART at CD4þ cell count at least 200 cells/ml were 13 percentage points more likely to be working at baseline (P<0.01, 95% confidence interval 0.06–0.21) than those initiating below this threshold. Those in the latter group achieved similar labor force participation rates within 1 year of initiating ART (P<0.01 on the time indicators). Both groups had similar asset scores at baseline and demonstrated similar increases in asset scores over the 6 years of follow-up. Conclusion: ART helps participants initiating therapy at CD4þ cell count below 200 cells/ml rejoin the labor force, though the findings for participants initiating with higher CD4þ cell counts suggests that pretreatment declines in labor supply may be prevented altogether with earlier therapy. Baseline similarities in asset scores for those with early and advanced disease suggest that mechanisms other than morbidity may help drive the relationship between HIV infection and economic outcomes.
Keywords: Antiretroviral therapy; CD4þ cell count; Economic restoration; Employment; HIV; Sub-Saharan Africa; Uganda; Wealth